The Epidemiology of Cancer-Associated Venous Thromboembolism: An Update - Mahajan, Anjlee; Brunson, Ann; White, Richard; Wun, Ted (Seminars in Thrombosis and Hemostasis, 2019)
The incidence of venous thromboembolism (VTE) is known to be higher in patients with malignancy as compared with the general population. It is important to understand and review the epidemiology of VTE in cancer patients because it has implications regarding treatment and prognosis. Multiple studies have shown that cancer patients who develop VTE are at higher risk for mortality. This article will focus on an update regarding the epidemiology of cancer-associated thrombosis (CT). The authors will describe factors associated with CT risk including cancer type and stage at the time of diagnosis, race and ethnicity, and cancer-directed therapy. In addition, recurrent thrombosis and the effect of thromboembolism on survival in cancer patients will also be addressed.
Keywords: venous thrombosis; cancer-associated thrombosis; pulmonary embolism; epidemiology